2018
DOI: 10.2196/formative.8248
|View full text |Cite
|
Sign up to set email alerts
|

User-Centered Design of a Mobile App for Weight and Health Management in Adolescents With Complex Health Needs: Qualitative Study

Abstract: BackgroundGrowing research has been conducted into the deployment and evaluation of mobile technology interventions for weight management in adolescents. However, no work has yet been conducted toward the development of these technologies for adolescents with complex health needs receiving specialized tertiary-level health care.ObjectiveThe aim of this study was to conduct a user-centered needs assessment of adolescents interested in weight management with complex health needs requiring specialized health care… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 68 publications
2
29
0
Order By: Relevance
“…Two recent studies utilize co-design approaches for the development of digital technologies to address adolescent overweight and obesity [ 56 , 57 ]. Through a co-design process to develop a smartphone app to support weight and health management, Rivera et al [ 56 ] were able to identify adolescents require personalized assistance with meal planning, including more convenient and efficient ways to plan meals and make healthier food choices throughout the day. This feature is not available in current commercial apps, which predominately focus on self-monitoring and caloric monitoring of food intake [ 58 ].…”
Section: Three Strategies For Effective Engagement With Digital Inmentioning
confidence: 99%
“…Two recent studies utilize co-design approaches for the development of digital technologies to address adolescent overweight and obesity [ 56 , 57 ]. Through a co-design process to develop a smartphone app to support weight and health management, Rivera et al [ 56 ] were able to identify adolescents require personalized assistance with meal planning, including more convenient and efficient ways to plan meals and make healthier food choices throughout the day. This feature is not available in current commercial apps, which predominately focus on self-monitoring and caloric monitoring of food intake [ 58 ].…”
Section: Three Strategies For Effective Engagement With Digital Inmentioning
confidence: 99%
“…The first differentiating category was tracking, logging, and making dietary recommendations [ 34 ]. A qualitative study for weight and health management design indicates that the core components of the app should include tailored meal recommendations and assistance with meal planning [ 35 ]. For the nutrition education feature, a review found that the most useful mobile health app would help the patient with lifestyle education, self-management, and designing a suitable diet [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Self-monitoring is the feature that has been identified in a number of reviews as the dominant feature in mobile app based weight management interventions (Pellegrini, et al, 2015;Zhao, et al, 2016;Payne, et al, 2015). A recent study found that 75% of top rated smartphone apps for weight loss were narrowly reliant on a food database and calorie tracking (Rivera, et al, 2018). Further to that observation Rivera et al (2018) found that their client group identified assistance with food planning as the key function in an app, with only 11% of apps providing this assistance.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that 75% of top rated smartphone apps for weight loss were narrowly reliant on a food database and calorie tracking (Rivera, et al, 2018). Further to that observation Rivera et al (2018) found that their client group identified assistance with food planning as the key function in an app, with only 11% of apps providing this assistance. Similarly, this lack of focus on meal planning as a potentially powerful behaviour change tool, has been overlooked in scientific study (Ducrot, et al, 2017) .…”
Section: Discussionmentioning
confidence: 99%